RESISTENSI PEREMPUAN DALAM DRAMA “SENANDUNG DAYANG DERMA” KARYA RINA NAZARUDDIN - Sri Sabakti (Madah: Jurnal Bahasa dan Sastra, 2014)
The play script "Senandung Dayang Derma (SDD)," by Rina Nazaruddin is a literary work that has much of Malay culture. Through characterization of Dayang Derma, the play script contains the perspective of feminism. The research on the script of  "SDD" aims to reveal the women resistance or attempt  in Malay culture. The approach used in this drama script analysis is feminist literary criticism by applying qualitative research methods. The results showed that women suffer oppression in Malay culture caused by a customary norms that in favor of the patriarchal ideology. The oppression of women is perceived as unfair because it all leads to  women inferior and showed mrn superior. Therefore, women make an effort or resistance to unfair treatment by doing resistance.